O potencial efeito da fragilidade física, cognitiva e imunológica sobre a mortalidade de nonagenários e centenários - Zuppa, Carina (2018)
Introduction: Fragility is one of the great syndromes in geriatrics, its pathogenesis acts in several interconnected systems in the body, physical, cognitive and immunological, compromises several physiological mechanisms and results in a poor prognosis for the patient. This condition mainly affects older elderly, nonagenarians and centenarians, little is known about the course of this syndrome and its outcomes in these populations more longevity. Our objective was to investigate the potential effect of physical, cognitive and immunological fragility on mortality in nonagenarians and centenarians of the city of Porto Alegre - Brazil. Method: This is a longitudinal follow-up study, composed of a representative sample of nonagenarians and centenarians from the city of Porto Alegre. At the first moment a questionnaire was applied for sociodemographic evaluation, health status, cognition and a physical evaluation to compose the criteria of physical and cognitive fragility. In a second moment, a blood collection was carried out in some patients to carry out immunological tests and the surplus of sample conditioned for future tests. Data on the mortality of these individuals were monitored for one year after completion of the evaluations. Results: A sample of 194 patients aged over 90 years was recruited; of this total, only 177 met the inclusion criteria for cognitive fragility, these individuals were classified into three groups: non-fragile 41, physical fragile 72 and fragile cognitive 64. No there were differences in socio-demographic data and health status between groups, but depressive symptoms were significantly present in fragile versus non-fragile individuals. Mortality was statistically frequent in individuals with cognitive fragility in relation to those who presented physical fragility and non-fragile individuals. The immunological data of the 52 individuals evaluated did not present significant differences between the groups. Conclusion: For the first time this research has shown great evidence that cognitive fragility is a better predictor of mortality in nonagenarians and centenarians. Survival during the follow-up period found in nonagenarians and centenarians with cognitive fragility was significantly lower than those with physical fragility and no frailty. According to our findings, cognitive fragility can be considered a better predictor of mortality than the physical fragility evaluated alone and from this information, since fragile people are great users of health and hospitalization resources, interventions focused on the cognitive fragility could improve quality of life and reduce the costs of care. Interfering early in cognitive fragility could change the negative outcomes in the evolution of fragility.